Two new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from Gerbilliscus guineae Thomas (Rodentia: Gerbillinae) in the Niokolo Koba National Park, Senegal - Modrý, David; Petrzelková, Klára; Jirků, Miloslav; Koubek, Petr (Systematic parasitology, 2008)
We describe two new species of Eimeria Schneider, 1875 from the gerbiline rodent Gerbilliscus guineae in the Niokolo Koba National Park, Senegal. Faecal examination of samples revealed the presence of sporulated oöcysts of two eimerian coccidia, both possessing an oöcyst residuum. Eimeria permira n. sp. is remarkable in terms of oöcyst size and oöcyst wall texture. Sporulated oöcysts are ellipsoidal, 45.8 (42-50) x 32.5 (31-38) mum; the oöcyst wall is 3-4 mum thick, composed of three layers, with the outer layer sheathed by rough granular material; and the sporocysts are broadly ellipsoidal, 15.4 (15-16) x 11 and with a Stieda body present. Oöcysts of Eimeria gerbillisci n. sp. are subspherical, 22.5 (19.5-24) x 18.8 (16.5-20) mum, with a colourless, faintly granulated oöcyst wall 1.5 thick; and the sporocysts are 10.1 (10-12) x 6.7 (6-8), broadly ellipsoidal and often somewhat pointed towards both ends.
Keywords: mikroskopie; Eimeria; Microscopy; zvířata; Species Specificity; Gerbillinae; Spores, Protozoan; feces; Animals; Senegal; druhová specificita; Feces; spory protozoální